2016
DOI: 10.1038/srep24896
|View full text |Cite
|
Sign up to set email alerts
|

Substantial and robust changes in microRNA transcriptome support postnatal development of the hypothalamus in rat

Abstract: MicroRNAs (miRNAs) modulate gene expression in male germ cells and somatic tissues of mammals on a genome-wide scale. Hundreds of miRNAs are encoded by mammalian genomes, a large fraction of which is expressed in brain. Here we have investigated the complexity and dynamics of miRNA transcriptomes that associate with neuronal network maturation of hypothalamic arcuate nucleus and median eminence (ARC/ME) in rat by analysing more than 300 miRNAs from 3–7 biological replicates at 5 postnatal time-points. The netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Individual cDNA libraries were built following an Illumina-like protocol in which 3′- and 5′-adapters were sequentially ligated at the 3′- and 5′-ends of small RNAs, respectively, to allow for their reverse transcription (RT) and amplification by polymerase chain reaction (PCR) as previously described (Doubi-Kadmiri et al, 2016 ). The 3′-Adaptor was first adenylated by using 25 pmoles of oligonucleotides, 2 × Quick Ligation reaction buffer (New England Biolabs), and 1,600 U of T4 DNA ligase (New England Biolabs), in a volume of 50 μl and by overnight incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual cDNA libraries were built following an Illumina-like protocol in which 3′- and 5′-adapters were sequentially ligated at the 3′- and 5′-ends of small RNAs, respectively, to allow for their reverse transcription (RT) and amplification by polymerase chain reaction (PCR) as previously described (Doubi-Kadmiri et al, 2016 ). The 3′-Adaptor was first adenylated by using 25 pmoles of oligonucleotides, 2 × Quick Ligation reaction buffer (New England Biolabs), and 1,600 U of T4 DNA ligase (New England Biolabs), in a volume of 50 μl and by overnight incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Different miRNAs have been related to peripheral controls of metabolisms (Vienberg et al, 2017 ). miRNA involvement in such functions at the ARC level has started to be explored and the possibility that miRNAs of ARC participate in the central control of energy homeostasis has yet to be characterized (Amar et al, 2012 ; Baroin-Tourancheau et al, 2014 ; Doubi-Kadmiri et al, 2016 ). Here, we have identified miRNA expression responses of ARC of adult male rats that had been submitted to perinatal and/or adult metabolic environmental challenges and consequently displayed differences in circulating levels of nutrients and hormones.…”
Section: Introductionmentioning
confidence: 99%
“…An epigenetic switch regulating the post‐transcriptional control of gene expression mediated by miRNAs has been described in inflammation‐related pathologies and it has even been proposed that lncRNA, which can code for miRNA, is an emergent modulator of the transcriptional activity of inflammatory response‐related genes . In the developing hypothalamus, important changes in the expression pattern of miRNAs have been described, suggesting the involvement of miRNAs in the functional organisation of the melanocortin system . Also, there is evidence showing that leptin, a hormone whose signal transduction pathway is downregulated in DIHI, modulates the hypothalamic expression of miRNAs and, conversely, miRNAs could modulate leptin signalling .…”
Section: New Cellular Mechanisms Involved In the Development Of Hypotmentioning
confidence: 99%
“…For instance, Zhang et al showed that 30 miRNAs including miR-7 and miR-191 are differentially expressed in the hypothalamus of the pig between stages P60, P120, and/or P180 (Zhang et al, 2013). More recently, a nice work showed robust changes in the expression of numerous miRNAs during the period of functional organization of the ARC and median eminence between stages P8–P14 and stages P21–P28 (Doubi-Kadmiri et al, 2016). …”
Section: The Microrna and The Melanocortin Systemmentioning
confidence: 99%